An introduction to Chinese civilization (New York : Columbia University Press, 1973)
A collection of essays that give a brief history of China and examine ten major aspects of Chinese civilization. Topics include Chinese anthropology, archaeology, art, economic trends, language, literature, and others.
Frontmatter -- Contributors -- Preface -- Note on Pronunciation -- Contents -- PART ONE. History of China -- I. Ancient Times and Classical Period / Meskill, John -- II. The First Imperial Period / Meskill, John -- III. The Period of Disunity / Meskill, John -- IV. The Second Imperial Period: Phase I / Meskill, John -- V. The Second Imperial Period: Phase II / Meskill, John -- VI. An Era of Foreign Rule / Meskill, John -- VII. The Third Imperial Period / Meskill, John -- VIII. The Breakdown of the Traditional Order / Meskill, John -- IX. Acceleration of the Pace of Change / Meskill, John -- X. The Revolutionary Period: The Contest for Primacy / Meskill, John -- XI. The Revolutionary Period: The Quest for Unity / Meskill, John -- PART TWO. Aspects of Chinese Civilization -- XII. China: An Anthropological Overview / Fried, Morton H. -- XIII. Chinese Archaeology / Chang, Kwang-Chih -- XIV. Chinese Art / Li, Chu-Tsing -- XV. Economic Structure of Traditional China / Chen, Nai-Ruenn -- XVI. Economic Trends in Modem China / Hou, Chi-Ming -- XVII, A Geographical View of China / Murphey, Rhoads -- XVIII. Political Institutions / Hucker, Charles O. -- XIX. The Chinese Language / Chu, Yu-Kuang -- XX. Chinese Literature / Watson, Burton -- XXI. The Role of Religion in Chinese Society / Yang, C. K. -- Appendix: Maps -- Acknowledgments -- Index
Includes bibliographical references.
In English.
Keywords: China -- Civilization